Primary School Character Education: A Sociology Review of Education - Rohib Adrianto Sangia; Hendra Kurniawan; I Nyoman Wijana; Fajar Muhamad Ramdan (ijd-demos, 2022)
AbstractThe findings of this study corroborate the researchers' assertion that many aspects of sociology will be examined to aid in the implementation of character education, one of which is the process of socialization, which is a critical factor in shaping and building the nation's character in society. Additionally, sociology is a social science field in which students will undoubtedly study about values and norms, human conduct, and social aberrations from social control. As seen through the lens of sociology, there are several major factors that have a significant impact on the development of a primary school student's character. The research approach employed is literature review, in which all available data is examined and presented from a variety of data additional papers in order to produce conclusions and a study. The data were gathered from materials in the form of books and other scholarly works pertaining to this topic.Keywords: Character, Sociology, Education, Primary School. AbstrakTemuan penelitian ini menguatkan pernyataan peneliti bahwa banyak aspek sosiologi yang akan dikaji untuk membantu pelaksanaan pendidikan karakter, salah satunya adalah proses sosialisasi, yang merupakan faktor kritis dalam membentuk dan membangun karakter bangsa di masyarakat. Selain itu, sosiologi adalah bidang ilmu sosial di mana siswa pasti akan mempelajari tentang nilai dan norma, perilaku manusia, dan penyimpangan sosial dari kontrol sosial. Dilihat dari kacamata sosiologi, ada beberapa faktor utama yang berdampak signifikan terhadap perkembangan karakter siswa sekolah dasar. Pendekatan penelitian yang digunakan adalah literature review, dimana semua data yang ada ditelaah dan disajikan dari berbagai data tambahan makalah guna menghasilkan kesimpulan dan kajian. Data dikumpulkan dari bahan-bahan berupa buku dan karya ilmiah lainnya yang berkaitan dengan topik ini.Kata kunci: Karakter, Sosiologi, Pendidikan, Sekolah Dasar.